Methods of teaching language and literature to develop language competence for Vietnamese students - Thi Ha, Trinh (Institute of Education and Social Research, 2023)
Developing language skills for students in Vietnam is an issue that needs attention. This article used interdisciplinary research methods between Linguistics and Education. Descriptive method was implemented to describe the characteristics of the Middle School Literature Program, the sixth grade Literature textbook set compiled. Analytical method was used to analyze the teacher's method of teaching literature and the linguistic abilities that need to be formed for students during this period. Developing this capacity is providing the most effective means to perfect thinking capacity. This article surveys teachers' Literature teaching methods applied to students at some Vietnamese schools with the aim of developing students' language and at the same time this will also be an information channel for completing Improve and criticize Literature textbooks compiled according to the new General Education Program (2018) in Vietnam that are in the early stages of being used.